2023
DOI: 10.3390/ma16052089
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of Average Avalanche Shapes for Acoustic Emission during Jerky Motion of Single Twin Boundary in Single-Crystalline Ni2MnGa

Abstract: Temporal average shapes of crackling noise avalanches, U(t) (U is the detected parameter proportional to the interface velocity), have self-similar behavior, and it is expected that by appropriate normalization, they can be scaled together according to a universal scaling function. There are also universal scaling relations between the avalanche parameters (amplitude, A, energy, E, size (area), S, and duration, T), which in the mean field theory (MFT) have the form E∝A3, S∝A2, S∝T2. Recently, it turned out tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…Furthermore, it was found that, t B R and a B A j in eqn (3), and thus scaling the voltage by A and the time by A (1Àj) , nice common functions were obtained for the motion of interfaces between austenite and martensite phases in ferromagnetic shape memory single crystals, 51 and for the motion of an individual twin boundary in a Ni 2 MnGa single crystal as well. 59 It was also shown that the value of j also appears in the scaling exponents x = 2 À j as well as y = 3 À j. 51 Since the experimental determination of j from the rising time versus amplitude relation is difficult (R is usually very short), we estimated j from the average values of x and y.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, it was found that, t B R and a B A j in eqn (3), and thus scaling the voltage by A and the time by A (1Àj) , nice common functions were obtained for the motion of interfaces between austenite and martensite phases in ferromagnetic shape memory single crystals, 51 and for the motion of an individual twin boundary in a Ni 2 MnGa single crystal as well. 59 It was also shown that the value of j also appears in the scaling exponents x = 2 À j as well as y = 3 À j. 51 Since the experimental determination of j from the rising time versus amplitude relation is difficult (R is usually very short), we estimated j from the average values of x and y.…”
Section: Resultsmentioning
confidence: 99%